The way of nagomi : the Japanese philosophy of finding balance and peace in everything you do - Mogi, Ken'ichirō, 1962- (The Experiment, LLC, 2023)
"This accessible guide to nagomi shows readers craving calm or fighting burnout a path to greater equanimity of mind"--